Asuhan Keperawatan pada Ny. A dan Ny. D yang Mengalami Gangguan Rasa Nyaman Nyeri dengan Post Sectio Caesarea atas Indikasi Masalah Sosial di RSUD Kota Bekasi - Sari, Shindi Kartika; Agustina, Agustina; Prihatini, Fitria (Jurnal Persada Husada Indonesia, 2024)
Nursing care for post partum caesarean section is delivery through an incision in the abdominal wall and uterine wall provided that the uterus is intact and the fetus weighs above 500 grams. This research uses a descriptive qualitative research method, with the aim of obtaining an overview of the implementation of nursing care for clients who experience pain in post Sectio Caesarea and to reduce pain in post Sectio Caesarea clients at the Bekasi City Regional Hospital. The results of the assessment of the two patients, namely Mrs. A and Mrs. D there are three similar diagnoses in patients, namely acute pain related to physical injurious agents, activity intolerance related to weakness, and risk of infection related to the effects of invasive procedures, nursing planning includes goals, outcome criteria, action plans and problem priorities in accordance with the theory in Mrs. A and Mrs. D. The first priority nursing diagnosis is acute pain related to a physical injurious agent. In general, it went smoothly because of good cooperation between the family and the room nurse who helped a lot in implementing the intervention. After carrying out 3x24 hour nursing actions, observing pain and providing deep breathing relaxation techniques, the nursing diagnosis for client 1 and client 2 was resolved. From the results of the study, only 3 diagnoses were the same as the theory, 2 different diagnoses, namely anxiety and ineffective breastfeeding because there were no visible signs and symptoms of these diagnoses.